Application of Calcbaba Comfort Theory in Nutritional Problems in Children with Cancer: Case Study - Sriasih, Ni Kadek; Allenidekania, Allenidekania; Hayati, Happy (Indonesian Journal of Global Health Research, 2023)
Chemotherapy is a cancer therapy that can prevent the development and spread of malignant cells, but causes various side effects (loss of appetite, nausea, vomiting, mucositis, changes in taste, pain, fatigue, dry mouth, diarrhea, constipation. These side effects result in discomfort for children with cancer, in more severe conditions it can worsen the child's nutritional status due to inadequate nutritional intake. Nursing care using the Kolcaba comfort approach can be applied to overcome children's discomfort cancer who experience nutritional imbalance problems. The method used is a case study. The comfort needs in the five management cases are assessed based on the physical, psychospiritual, environmental and sociocultural contexts. The comfort interventions provided include standards of comfort, coaching, and comfort food for the soul . Nursing evaluation of the problem of nutritional imbalance which is a physical aspect of the patient, namely, the comfort type for the five children is ease comfort and three of the five children also have transcendence type comfort for other aspects. Kolcaba's Comfort Theory can be applied to pediatric cancer patients who experience nutritional disorders and provides opportunities for nurses to develop innovative interventions to improve the quality of nursing care.